2017
DOI: 10.1016/j.najef.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning about individual managers’ performance in UK pension funds: The importance of specialization

Abstract: This study examines the performance of managers over time, as well as its persistence, taking into account both manager characteristics and market conditions. Applying parametric and non-parametric methodologies, we examine a sample of UK equity pension fund managers. Our results help to understand the importance of manager assignments in the industry and reveal the importance and benefits of management specialization. We find certain manager performance persistence, revealing that some managers are better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
2
7
0
2
Order By: Relevance
“…In addition, a study by Alda et al [5] adopted the CAPM and Carhart 4-Factor model and indicates the outperformance of the U.K pension funds and only the momentum factor is negative whereas the other factors are positive. Moreover, the study has also incorporated personal traits like gender and the experience of fund managers, and it was found that these personal traits do not have any significant impact on funds' performance, while management strategy such as specialization skill enables the managers to perform better than do the generalized managers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study by Alda et al [5] adopted the CAPM and Carhart 4-Factor model and indicates the outperformance of the U.K pension funds and only the momentum factor is negative whereas the other factors are positive. Moreover, the study has also incorporated personal traits like gender and the experience of fund managers, and it was found that these personal traits do not have any significant impact on funds' performance, while management strategy such as specialization skill enables the managers to perform better than do the generalized managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, private pension funds may be the appropriate saving vehicles that could complement the retirement savings of retirees. Nevertheless, there is only little empirical evidence found to support this idea as only Chu and McKenzie [5] have shown the outperformance of equity pension funds in Hong Kong. Hence, despite the empirical evidence of the outperformance of pension funds in developed countries like the U.K and U.S (Coggin et al [3], Adami et al [4] and Alda et al [5]), the presence of superiority of pension funds in Asia is not proven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A idade se mostrou significante em duas formas de mensurar o desempenho com sinais opostos, sendo negativo (Berggrun et al,2014;Mendonça et al, 2017;Silva et al, 111 2018) para o Alfa de Jensen e positivo (Milani & Ceretta, 2013;Alda, Andreu, & Sarto, 2017) para o retorno anual, podendo indicar que, em alguns casos, a idade do FIA representa sua sobrevivência no mercado e o prestígio do ponto de vista de seus investidores (Golec, 1996). (Bertin & Prather;2009;Golec, 1996).…”
Section: Corrupunclassified
“…Idade do Fundo (AGE) -Logaritmo natural da idade do Fundo no início de cada ano da amostra. Considerando que estudos anteriores apontam tanto relação positiva (Golec, 1996;Milani & Ceretta, 2013;Alda, Andreu, & Sarto, 2017) quanto negativa para essa variável (Berggrun, Mongrut, Umana, & Varga, 2014;Mendonça, Campani, & Leal, 2017;Silva et al, 2018), o sinal esperado é indefinido.…”
unclassified